2021
DOI: 10.1007/s10597-020-00737-x
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gap: Increasing Community Mental Health Services in Rural Indiana

Abstract: Due to the significant need for mental health services in rural Martin County, IN and lack of providers, this study examined the current strengths of the community as well as the barriers preventing mental health service delivery. The goal of the study was to propose community-specific solutions to overcoming the barriers. Using a strengths-based approach (Saleeby in The strengths perspective in social work practice, Longman, White Plains, NY, 1992), the authors first sought to understand Martin County residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Even when farmers described scenarios in which they would consider going to therapy or a similar intervention, they expressed concerns about their privacy and the negative impact that publicly seeking care for a mental health disorder would have on other community members’ perceptions. These themes are consistent with previous literature illustrating barriers to mental health care in rural areas and underutilization of existing services (Schultz et al, 2021). Many of the farmers were still seeing the same family doctors they had seen their entire lives and worried about disclosing mental health information to someone they see at church or around their hometown.…”
Section: Discussionsupporting
confidence: 91%
“…Even when farmers described scenarios in which they would consider going to therapy or a similar intervention, they expressed concerns about their privacy and the negative impact that publicly seeking care for a mental health disorder would have on other community members’ perceptions. These themes are consistent with previous literature illustrating barriers to mental health care in rural areas and underutilization of existing services (Schultz et al, 2021). Many of the farmers were still seeing the same family doctors they had seen their entire lives and worried about disclosing mental health information to someone they see at church or around their hometown.…”
Section: Discussionsupporting
confidence: 91%
“…Participants in our study talked extensively about staff recruitment and retention challenges in their counties and how limited workforce capacity results in large caseloads, burnout, and lower quality services delivered to clients. This finding is strongly supported in research studies and reports and is widespread in rural areas across the country (Baum & King, 2020;Buche et al, 2017;Gale et al, 2019;Schultz et al, 2021). These studies and reports recommend incentives to increase the size of the workforce including higher salaries; flexible hours; additional residency slots; and loan repayment, pipeline, and relocation and resettlement programs (Baum & King, 2020;Buche et al, 2017).…”
Section: Limited Workforce Capacity and Burnoutmentioning
confidence: 81%
“…This created stress, undervaluation, burnout, and turnover. Therefore, though burnout and turnover among rural providers are well-studied concepts (e.g., Gale et al, 2019;Schultz et al, 2021), our study identified a restrictive quota system as a contributor which suggests that the way service quotas are determined to be revised to address the unique needs of each county and population.…”
Section: Restrictive State Policies Approaches and Regulationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Authors of a rapid review identified 31 mobile apps and 114 web-based resources (e.g., telemedicine) that could be used to support mental health for Canadians during the pandemic ( Strudwick et al, 2021 ). Many barriers exist to accessing these resources, including awareness, cost and connectivity and these may be responsible for reported high priority but lack of completion of mental health checks in this study ( Schultz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%